Pengaruh Tingkat Pendapatan Dan Pemahaman Peraturan Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Di Masa Pandemi Covid-19 (Studi Kasus Pada Wajib Pajak Orang Pribadi Di KPP Pratama Bekasi Barat) - Felya Agata Beddu; Diana Prihadini; Rianto Rianto (Jurnal Ilmu Administrasi Publik, 2021)
The COVID-19 pandemic has caused economic growth in Indonesia to contract to 2.07% (c-to-c), one of the things that support economic income in Indonesia is tax revenue, but the state tax revenues in 2018 - 2020 always declined and the realization SPT compliance of individual taxpayers at West Bekasi Small Tax Office has never been on target. The purpose of this study was to analyze the effect of income level and understanding of tax regulations on individual taxpayer compliance during the covid-19 pandemic. This study used quantitative research methods with data collection techniques in the form of questionnaires and used 2 independent variables: income level and understanding of tax regulations and 1 dependent variable: Taxpayer Compliance. The population of this research was individual taxpayers at West Bekasi Small Tax Office using a non-probability sampling technique with a total sample of 103 samples by using the slovin formula. This study also employed Multiple linear regression analysis with computer assistance through IBM Statistics 26.0 software for Mac Big.Sur. The results of the study found that the level of income has an effect on taxpayer compliance by 46.6% and understanding of tax regulations has an effect on taxpayer compliance by 53.9%. The level of income and understanding of tax regulations together affect taxpayer compliance by 59.5% and 40.5% is influenced by other factors outside of this study.